2010
DOI: 10.2337/db10-0365
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Increases Lysyl Oxidase Expression and Activity in Retinal Endothelial Cells: Mechanism for Compromised Extracellular Matrix Barrier Function

Abstract: OBJECTIVEIn diabetes, retinal vascular basement membrane (BM) undergoes significant thickening and compromises vessel function including increased vascular permeability, a prominent lesion of early diabetic retinopathy. In this study we determined whether altered expression and activity of lysyl oxidase (LOX), a cross-linking enzyme, may compromise vascular basement membrane functional integrity under high-glucose (HG) conditions.RESEARCH DESIGN AND METHODSRat retinal endothelial cells (RRECs) grown in normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 50 publications
7
54
0
1
Order By: Relevance
“…Most recent findings [187][188][189] provide a sufficient basis for the speculation that the different degrees of susceptibility of enteric neurons and microvessels to a pathological stimulus such as hyperglycemia might be related to the prevalence of bacteria in the different parts of the GI tract. Accordingly, the differences in prevalence of bacteria in different gut segments [188,190] are influenced by the oxygen supply of the small and large intestine [191] . Knowledge of species and functional composition of the gut microbiome is rapidly increasing thanks to technological advances in culture independent methods [189,[192][193][194][195] .…”
Section: Discussionmentioning
confidence: 99%
“…Most recent findings [187][188][189] provide a sufficient basis for the speculation that the different degrees of susceptibility of enteric neurons and microvessels to a pathological stimulus such as hyperglycemia might be related to the prevalence of bacteria in the different parts of the GI tract. Accordingly, the differences in prevalence of bacteria in different gut segments [188,190] are influenced by the oxygen supply of the small and large intestine [191] . Knowledge of species and functional composition of the gut microbiome is rapidly increasing thanks to technological advances in culture independent methods [189,[192][193][194][195] .…”
Section: Discussionmentioning
confidence: 99%
“…Chemically induced DM lacks specificity; has deleterious effects on the kidney, lung and liver; may cause tumors or necrosis; 90,91 and may lead to erroneous conclusions. Exposure to high concentration of glucose is widely used in cell-culture models of DM, [92][93][94] but there are no data showing that this method can be used to induce hyperglycemia in rodents. Most importantly, the immersion-induced diabetic zebrafish model mimics the fluctuations in blood glucose levels of human diabetic patients, who respond to dietary changes and insulin injections.…”
Section: Diabetic Zebrafishmentioning
confidence: 99%
“…Transcription and expression of the upstream transcription factor, hypoxia inducible factor 1 (HIF-1), is elevated by HG in mouse BMVECs and associated with down regulation of occludin and ZO-1 (Chronopoulos et al, 2010; Tien et al, 2014). A blockade of VEGF in these cells ameliorated the downstream impact on TJs, suggesting that VEGF is produced by BMVECs in response to HIF-1 and acts in an autocrine/paracrine fashion to increase BBB permeability (Figure 2).…”
Section: Endothelial Cell Dysfunctionmentioning
confidence: 99%
“…Therefore, Cx43 down-regulation may contribute to the dysfunction of the blood-retina barrier through vascular permeability in diabetic retinopathy. Though this effect is best characterized in retinal tissue, several studies have demonstrated a significant role for Cx43 in regulation of TJ proteins, such as occludin, at the BBB (Chronopoulos et al, 2010), and ZO-1 in kidney (Xie et al, 2013). …”
Section: Pericyte Dysfunctionmentioning
confidence: 99%